MODERN APPROACHES FOR THE DIAGNOSTICS AND TREATMENT OF NEWBORNS WITH ANORECTAL ATRESIAS (LITERARY DATA AND OWN EXPERIENCE) - O.M. Gorbatyuk; I.A. Makedonsky (Bukovynian State Medical University, 2020)
Summary. The article is devoted to the problem of anorectal atresias in newborns, which are widespread and ranked first among the causes of disability in children. Based on the results of literature and our own experience, modern approaches to the diagnosis and treatment of congenital anomalies in newborns are presented. The 37 article presents epidemiology, modern views on diagnostics and treatment of main pathology and its complications in newborns. The necessity of improvement and wide introduction of prenatal diagnostics of anorectal atresias as an effective non-invasive method of early diagnostics of pathology is substantiated. The necessity of introduction of a complex of preventive measures at dirth defects, support of modern medical strategies and application of technically advanced methods of correction of a defect are emphasized. Generalization of own experience and modern approaches to the diagnosis, treatment and prevention of birth defects in newborns will be of great theoretical and practical importance for pediatric surgeries who are engaged in the issues of early detection of congenital malformations and their treatment, and to facilitate the coordination of specialists' efforts in improving the effectiveness of prenatal diagnosis of congenital anomalies and reducing lethality